Validation and Final Results from the First Cardiac Lead Post-Approval Study Using Real-World Data - Mullane S; Hicks JB; Sharmin K; Harrell C; Rock A; Miller C (Pragmatic and Observational Research)
Steven Mullane,1 Jacob B Hicks,2 Kazi Sharmin,1 Camden Harrell,1 Angie Rock,1 Crystal Miller1 1BIOTRONIK Inc., Lake Oswego, OR, 97035, USA; 2BIOTRONIK NRO INC., Lake Oswego, OR, 97035, USACorrespondence: Steven Mullane, BIOTRONIK, Inc., 6024 Jean Road, Lake Oswego, OR, 97070, USA, Tel +503-201-3892, Email steven.mullane@biotronik.comBackground: As part of Electrophysiology Predictable and Sustainable Implementation of National Registries (EP PASSION), a multi-stakeholder collaboration between the US Food and Drug Administration (FDA), academic and society partners, and cardiovascular implantable electronic device manufacturers, a 5-year bradycardia lead study transitioned from a traditional post-approval study (PAS) to a real-world data (RWD) approach using a novel method to evaluate chronic cardiac lead complications.Methods: Lead complications were identified using a combination of diagnosis and procedure codes from 2013 to 2020 fee-for-service Medicare claims data along with BIOTRONIK device registration and Medical Device Reporting data from patients implanted between 2013 and 2015 with a Solia S lead. A proof-of-concept analysis was performed using McNemar’s test to compare lead complications reported in the traditional PAS with lead complications identified in the RWD. Kaplan–Meier survival and incidence rates were evaluated to determine real-world long-term safety.Results: The proof-of-concept analysis of 896 patients found in both traditional PAS and RWD sources demonstrated a 99.7% proportion of overall agreement in identifying lead complications (p = 0.0833). Following this validation, 1841 study leads from 1015 Medicare patients were analyzed. A total of 33 lead complications (attributable or possibly attributable to the study lead) were identified for a rate of 0.005 complications per lead-year. The complication-free rate at 5-years post-implant was 97.2% (95% CI: 96.07%, 98.06%).Conclusion: These results led to the first FDA approval for transition of a cardiac lead PAS to long-term safety reporting using RWD, paving the way for future real-world cardiac lead and device surveillance studies.ClinicalTrials.gov Identifier: NCT01791127.Keywords: real-world data, real-world evidence, cardiac lead, pacemaker